Zeta Functions in Geometry
DOI: 10.2969/aspm/02110033
|View full text |Cite
|
Sign up to set email alerts
|

Fonctions Zêta de Selberg et Surfaces de Géométrie Finie

Abstract: L'accès aux archives de la revue « Séminaire de Théorie spectrale et géométrie » implique l'accord avec les conditions générales d'utilisation (http://www.numdam.org/conditions). Toute utilisation commerciale ou impression systématique est constitutive d'une infraction pénale. Toute copie ou impression de ce fichier doit contenir la présente mention de copyright.Article numérisé dans le cadre du programme Numérisation de documents anciens mathématiques http://www.numdam.org/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 6 publications
1
30
0
2
Order By: Relevance
“…In this section we extend some of the results of [12] and [13], obtained in the case of Riemann surfaces, to asymptotically hyperbolic manifolds. We show that the kernel of the Poisson operator is a multiple of the Eisenstein function and, as in [12], we obtain a formula for the scattering matrix in terms of the resolvent. (Similar results have been established by Borthwick in [7] for ℜζ = n/2.)…”
Section: The Poisson Operator and The Scattering Matrixmentioning
confidence: 75%
See 3 more Smart Citations
“…In this section we extend some of the results of [12] and [13], obtained in the case of Riemann surfaces, to asymptotically hyperbolic manifolds. We show that the kernel of the Poisson operator is a multiple of the Eisenstein function and, as in [12], we obtain a formula for the scattering matrix in terms of the resolvent. (Similar results have been established by Borthwick in [7] for ℜζ = n/2.)…”
Section: The Poisson Operator and The Scattering Matrixmentioning
confidence: 75%
“…This is the analogue of Definition 2.2 of [12]. For simplicity we will work with the definition given by (4.2) and so we fix a product decomposition X ∼ ∂X × [0, ǫ) of X near ∂X.…”
Section: The Poisson Operator and The Scattering Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…In [38] (see also [42]) it was shown that the infinite product converges for Re(s) > δ Γ , and that the Selberg zeta function has a meromorphic continuation to all of C. In the special case of surfaces this was also proved in [17]. Partial results concerning the logarithmic derivative of the Selberg zeta function have been obtained in [34] for δ Γ < 0 and in [41] in the general case.…”
Section: Introductionmentioning
confidence: 99%